Evaluasi Pengelolaan Keuangan Desa Berdasarkan Asas Transparan, Akuntabel, Partisipatif, Tertib Dan Disiplin Anggaran (Studi Kasus Pada Desa Puubenua, Kec. Baula, Kab. Kolaka) - Nichen .; Sriayu Pracita; La Ode Turi (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
This research aimed to find out the financial management of Puubenu village, Baula, Kolaka which had been evaluated based on its transparancy, accountability, participation, also discipline and accurate budgetting The research was qualitative While, the instrument in data collection used interview and documentation with a theme that focused to village financial management, transparency basis, accountability basis, participation basis, discipline and accurate budgetting implementation basis. Moreover, the data analysis technique used triangulation, and then with comparation of some indicators such as: transparant, accountable, participative, discipline and accurate budgetting The research result concluded the village focal government of Puubenua had implemented each of village financial management stages properly, and suitably with transparancy, accountability, participation, alse its discipline and accurate budgetting However, there were problems namely the application of Village Financial System (SISKEUDES) which was not optimally used and lack of village officials competence in using the app Therefore, there were some solutions, budgetting the cost of internet networking installation which was adequately Besides, having the training and regular assistance from related agencies in order to increase village officials competence.